Creating vessel elements in vitro: Towards a comprehensive understanding of the molecular basis of xylem vessel element differentiation - Tan, Tian Tian (Plant Biotechnol (Tokyo), 2019)
Xylem is an essential conductive tissue in vascular plants, and secondary cell wall polymers found in xylem vessel elements, such as cellulose, hemicellulose, and lignin, are promising sustainable bioresources. Thus, understanding the molecular mechanisms underlying xylem vessel element differentiation is an important step towards increasing woody biomass and crop yields. Establishing in vitro induction systems, in which vessel element differentiation is induced by phytohormonal stimuli or by overexpression of specific transcription factors, has been vital to this research. In this review, we present an overview of these in vitro induction systems, and describe two recently developed in vitro induction systems, VISUAL (Vascular cell Induction culture System Using Arabidopsis Leaves) and the KDB system. Furthermore, we discuss the potentials and limitations of each of these new in vitro induction systems for advancing our understanding of the molecular mechanisms driving xylem vessel element differentiation.